PEMIKIRAN DAKWAH BAIDUZZAMAN SAID NURSI - Haryanti, Umi; Supriadin J, Irwan (JEMARI : Jurnal Edukasi Mahasiswa Sunan Giri, 2024)
This article discusses Bediuzzaman Said Nursi's thoughts on da'wah, emphasizing Risale-i Nur as the foundation of the da'wah movement and the development of a modern Islamic community. This study uses a literature review method, analyzing various primary and secondary literature related to Nursi's works and the socio-political context of Turkey at that time. The results of the study show that Nursi's thoughts contain four main concepts: Murasalah as a form of tabligh to spread the Risale-i Nur; Ustadhiyyah al-Qur'an as the basis for change (taghyir) towards spiritual and social transformation; al-Shahs al-Ma'nawi as a form of takwin al-ummah in strengthening solidarity and amar ma'ruf nahi munkar; and al-Fana' fi al-Ikhwan as a principle of brotherhood in realizing khairiyyah al-ummah. These concepts emphasize that Nursi's da'wah does not only focus on ritual aspects, but also on building a community with noble character that is progressive and responsive to the challenges of modernity. Thus, Said Nursi's thoughts are relevant to be used as a paradigm for contemporary da'wah in building an Islamic civilization based on the Qur'an, Sunnah, and communitarian values.